Photobiomodulation effect of red LED (630 nm) on the free radical levels produced by pulp cells under stress conditions - Bonvicini, Jéssica Fernanda Sena; Basso, Fernanda Gonçalves; de Souza Costa, Carlos Alberto [UNESP]; Soares, Carlos José; Turrioni, Ana Paula (Springer Nature, 2021)
The aim of this study was to assess the ability of red light emitting diodes (LED) to modulate oxidative stress in human dental pulp fibroblasts (HDPFs) when different irradiation parameters are employed. Cells from primary teeth were seeded (100,000 cells/well) in 24-well plates in culture medium (DMEM). At 24 h after incubation, the culture medium was replaced with DMEM containing 10 μg/mL lipopolysaccharide (LPS). Thereafter, the cells were irradiated (LED 630 nm, 0.04 W/cm2 and 0.08 W/cm2) at 0 J/cm2 (control group), 4 J/cm2, 15 J/cm2, and 30 J/cm2; and their viability (MTT assay), number (Trypan Blue), synthesis of nitric oxide (NO) (Griess reagent), and reactive oxygen species (ROS) (fluorescence probe, DCFH-DA) were assessed. The Kruskal-Wallis and Mann-Whitney statistical tests using Bonferroni correction were employed (significance level of 5%). Compared to that in control fibroblasts, increased viability was observed in HDPFs exposed to LPS and irradiated with 15 J/cm2 and 30 J/cm2 at 0.04 W/cm2 and 4 J/cm2 and 15 J/cm2 at 0.08 W/cm2 (p < 0.05). Exposure to 4 J/cm2 at 0.04 W/cm2 and 15 J/cm2 and 30 J/cm2 at 0.08 W/cm2 modulated the oxidative stress in cells relative to that observed in non-irradiated LPS-treated pulp cells (p < 0.05). It was concluded that the irradiation strategies of using red LED with radiant exposures of 15 J/cm2 and 30 J/cm2 at 0.04 W/cm2 and 15 J/cm2 at 0.08 W/cm2 were the best parameters to decrease NO and ROS concentration and to stimulate viability of HDPFs exposed to LPS challenge.
Keywords: Cell culture; Dental pulp; Oxidative stress; Photobiomodulation